Multiple arterial anomalies in upper limb - Baral, P; Vijayabhaskar, P; Roy, S; Kumar, S; Ghimire, S; Shrestha, U (Kathmandu University Medical Journal, 2010)
An isolated neurovascular variation is common but multiple vascular anomalies on same upper limb is a very rare case. We observed an unusual variations in right upper limb during routine dissection of a Nepali cadaver. The variations were observed in Axilla, Forearm and Palm. In axilla, first part of axillary artery did not give any branch, the second part of axillary artery gave off only two branches - (a) thoracoacromial artery and (b) a large common trunk which later gave off lateral thoracic, thoracodorsal, subscapular, posterior circumflex scapular and then continued as posterior circumfl ex humeral artery. The third part of axillary artery gave off only anterior circumflex humeral artery. In forearm, the ulnar artery runs downward superficial to flexor muscles. Here, radial artery gave off common interosseous artery. In palm radial artery did not give any contribution to superficial palmar arch which is solely formed by the continuation of ulnar artery. This type of anomalies are very rare and is not reported in Nepalese cadaver at all. These anomalies are described in detail and their clinical relevance is highlighted. Key words: Axillary artery; Brachial artery; Radial artery; Ulnar artery; Palmar arch; Variations DOI: 10.3126/kumj.v7i3.2740 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 293-297